New ribosome-inactivating proteins and other proteins with protein synthesis–inhibiting activities - Wong, Jack Ho; Bao, Hui; Ng, Tzi Bun; Chan, Helen Hei Ling; Ng, Charlene Cheuk Wing; Man, Gene Chi Wai; Wang, Hexiang; Guan, Suzhen; Zhao, Shuang; Fang, Evandro Fei; Rolka, Krzysztof; Liu, Qin; et al. (Applied microbiology and biotechnology, 2020)
Ribosome-inactivating proteins (RIPs) consist of three varieties. Type 1 RIPs are single-chained and approximately 30-kDa in molecular weight. Type 2 RIPs are double-chained and composed of a type 1 RIP chain and a lectin chain. Type III RIPs, such as maize b-32 barley and JIP60 which are produced as single-domain proenzymes, possess an N-terminal domain corresponding to the A domain of RIPs and fused to a C-terminal domain. In addition to the aforementioned three types of RIPs originating from flowering plants, there are recently discovered proteins and peptides with ribosome-inactivating and protein synthesis inhibitory activities but which are endowed with characteristics such as molecular weights distinctive from those of the regular RIPs. These new/unusual RIPs discussed in the present review encompass metazoan RIPs from Anopheles and Culex mosquitos, antimicrobial peptides derived from RIP of the pokeweed Phytolacca dioica , maize RIP (a type III RIP derived from a precursor form), RIPs from the garden pea and the kelp. In addition, RIPs with a molecular weight smaller than those of regular type 1 RIPs are produced by plants in the Cucurbitaceae family including the bitter gourd, bottle gourd, sponge gourd, ridge gourd, wax gourd, hairy gourd, pumpkin, and Chinese cucumber. A small type II RIP from camphor tree ( Cinnamomum camphora ) seeds and a snake gourd type II RIP with its catalytic chain cleaved into two have been reported. RIPs produced from mushrooms including the golden needle mushroom, king tuber mushroom, straw mushroom, and puffball mushroom are also discussed in addition to a type II RIP from the mushroom Polyporus umbellatus . Bacterial (Spiroplasma) RIPs associated with the fruitfly, Shiga toxin, and Streptomyces coelicolor RIP are also dealt with. The aforementioned proteins display a diversity of molecular weights, amino acid sequences, and mechanisms of action. Some of them are endowed with exploitable antipathogenic activities.